Exploring Teachers’ and Students’ Perspectives on Teaching Vocabulary Through Word Puzzle Games - M. Faldi Rizkinta Sembiring; Nazli Fahada; Surya Kelana Putra (LPPPI Publishing, 2026)
This study investigates teachers’ and students’ perspectives on the use of word puzzle games in teaching English vocabulary at SMP Swasta Methodist 9 Medan. The research aims to explore how these games are implemented and how they influence students’ vocabulary learning. A qualitative descriptive approach was employed, involving one English teacher and 23 eighth-grade students. Data were collected through semi-structured interviews, classroom observations, and documentation. The data analysis process included data preparation, reading and reflection, coding and categorization, and theme development. The findings reveal that word puzzle games were effectively implemented as a student-centered learning activity that enhanced classroom engagement and reduced monotony in vocabulary instruction. Both the teacher and students expressed positive perceptions toward the use of these games. Students reported increased motivation, improved vocabulary understanding, better collaboration, and greater confidence in learning. Meanwhile, the teacher perceived word puzzle games as a valuable tool to support vocabulary mastery, stimulate critical thinking, and foster a positive and interactive classroom environment. However, several challenges were identified, including variations in students’ proficiency levels, time management constraints, classroom noise, and the need for thorough preparation. Despite these challenges, the study concludes that word puzzle games serve as an effective gamification strategy in teaching vocabulary when supported by proper planning and effective classroom management.